Evaluation of a Flipped Classroom Model: A Case Study from Oman. Issue 1 (March 2020) - Pandow, Bilal Ahmad; Inan, Nihan Kutahnecioglu; S., Ananda
Abstract: The flipped learning approach over the years has gained importance, especially in higher educational establishments that primarily focus on more personalized learning for the students. In this context, the current study evaluates a flipped learning approach which was implemented by a higher education institution from the Middle East region as a pilot project and analyses the impact of the flipped approach on the student performance from the educators' perspective. The study focuses on different aspects like the impact of the flipped approach on student performance in a different type of assessments, the impact of the flipped approach on academic performance, learning and development, and academic support activities. Also, this article analyses whether flipped learning reduces the plagiarism cases, impact on student attendance, student participation in extracurricular activities, impact on student's knowledge, influence on student collaboration, effect on improvement in the ability to solve problems and impact of this approach on helping students to take the responsibility of their learning and become self-learners. This study empirically identified the learning outcomes from a flipped class and provides recommendations for the educators and higher education institutions for successful implementation of the flipped learning approach.